Differentiability of the Efficient Frontier when Commitment to Risk Sharing is Limited - Thorsten Koeppl (Queen's University, Department of Economics, 2004)
This paper shows that the value function describing efficient risk sharing with limited commitment is not necessarily differentiable everywhere. We link differentiability of the value function to history dependence of efficient allocations and provide sufficient conditions for both properties.
Keywords: C61; E21; 330; Risk Sharing; Limited Commitment; Differentiability of Efficient Frontier; Risiko; Allokation; Theorie